2017
DOI: 10.1177/1177625017690133
|View full text |Cite
|
Sign up to set email alerts
|

Modeling fructose-load-induced hepatic de-novo lipogenesis by model simplification

Abstract: Hepatic de-novo lipogenesis is a metabolic process implemented in the pathogenesis of type 2 diabetes. Clinically, the rate of this process can be ascertained by use of labeled acetate and stimulation by fructose administration. A systems pharmacology model of this process is desirable because it facilitates the description, analysis, and prediction of this experiment. Due to the multiple enzymes involved in de-novo lipogenesis, and the limited data, it is desirable to use single functional expressions to enca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Authors found that Pb2+ exposure could be a lethal disruptor of lipid metabolism in hepatocytes, and highlighted sorcin (a cytosolic adaptor partner of carbohydrate responsive element binding protein (ChREBP)-dependent hepatic lipogenesis) as a novel therapeutic target against Pb2+-induced hepatic dyslipidemia [90]. Hepatic de-novo lipogenesis (DNL) is a metabolic process proposed in the pathogenesis of T2DM, with multiple enzymes involved in this process [91].…”
Section: New and Alternative Mechanismsmentioning
confidence: 99%
“…Authors found that Pb2+ exposure could be a lethal disruptor of lipid metabolism in hepatocytes, and highlighted sorcin (a cytosolic adaptor partner of carbohydrate responsive element binding protein (ChREBP)-dependent hepatic lipogenesis) as a novel therapeutic target against Pb2+-induced hepatic dyslipidemia [90]. Hepatic de-novo lipogenesis (DNL) is a metabolic process proposed in the pathogenesis of T2DM, with multiple enzymes involved in this process [91].…”
Section: New and Alternative Mechanismsmentioning
confidence: 99%
“…Relevant in silico simulations have been reported, including glucose absorption and transportation, hormonal regulation, zonation effects, and the relationship between glucose intake and high-intensity exercise, lipid metabolism in addition to metabolic diseases (Chalhoub et al, 2007a , b ; Hetherington et al, 2012 ; König et al, 2012 ; Sumner et al, 2012 ; Ashworth et al, 2016 ; Naftalin, 2016 ; Noorman et al, 2019 ). Irrespective of the fact that abundant studies have highlighted the important role fructose metabolism plays in metabolic diseases, only a few models have placed emphasis on the fructose metabolism and none of these have reflected the potentially dynamic changes (Allen and Musante, 2017 , 2018 ; Maldonado et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%